2007
DOI: 10.1126/science.1136371
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of the Properties of Water from First Principles

Abstract: A force field for water has been developed entirely from first principles, without any fitting to experimental data. It contains both pairwise and many-body interactions. This force field predicts the properties of the water dimer and of liquid water in excellent agreement with experiments, a previously elusive objective. Precise knowledge of the intermolecular interactions in water will facilitate a better understanding of this ubiquitous substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
330
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 391 publications
(339 citation statements)
references
References 34 publications
9
330
0
Order By: Relevance
“…Calculations on the effects of monomer flexibility [18][19][20] have shown that this quantity a͑0͒ + a͑1͒ decreases when the H 2 O monomers are relaxed. It is striking in this respect, see Table VI, that the other pure ab initio potential that gives very good agreement with the experimental data, the 6D CC-pol potential, 10,17,21 gives practically the same deviation from experiment for a͑0͒ + a͑1͒ as the HBB0 and HBB potentials. It is most probable that all of these potentials have reached the "rigid monomer limit" of the acceptor splitting.…”
Section: Vibration-rotation Tunneling Spectrum Of the Water Dimersupporting
confidence: 66%
See 1 more Smart Citation
“…Calculations on the effects of monomer flexibility [18][19][20] have shown that this quantity a͑0͒ + a͑1͒ decreases when the H 2 O monomers are relaxed. It is striking in this respect, see Table VI, that the other pure ab initio potential that gives very good agreement with the experimental data, the 6D CC-pol potential, 10,17,21 gives practically the same deviation from experiment for a͑0͒ + a͑1͒ as the HBB0 and HBB potentials. It is most probable that all of these potentials have reached the "rigid monomer limit" of the acceptor splitting.…”
Section: Vibration-rotation Tunneling Spectrum Of the Water Dimersupporting
confidence: 66%
“…There has been great progress in realizing this goal recently. 10 Here, we report additional and significant progress in this effort.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the new excited A-E state wave functions are more localized than are the ground state A-E wave functions. Olthof et al 12 calculated the splittings due to umbrella inversion of the para monomer in the ammonia …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we hope that the present study will motivate detailed study of the ammonia dimer by a similar combination of state of the art dynamics and potential models, such as the ones recently published for the water dimer. 10,12 This would greatly accelerate our understanding of this important prototype system. The internal coordinate system of the ammonia dimer.…”
Section: Methodsmentioning
confidence: 97%
“…Reference 25 reviews the work up to the year 2000. Several ab initio water pair potentials have been obtained recently, with [26][27][28][29] or without 30,31 explicit inclusion of the polarization effects that form the dominant contribution to the many-body interactions in water. These water pair potentials were tested by a computation 29,31 of the vibration-rotation-tunneling ͑VRT͒ levels of the water dimer and comparison with the available high-resolution terahertz spectra.…”
Section: Introductionmentioning
confidence: 99%